Three-dimensional Determination of Dental Occlusion and Facial Structures using Soft Tissue Cephalometric Analysis - Adaskevicius, R.; Vasiliauskas, A. (Elektronika ir Elektrotechnika, 2012)
A high accuracy 3D structured-light scanning system and method for integration of 3D digital dental cast models and human face model is proposed. The original two cameras and DLP projector system for surface 3D reconstruction is designed. The techniques for alignment of 3D human face model with the 3D dental cast models according their location and orientation in a mouth is presented. This technique allows evaluation of morphological parameters used for treatment planning and gives to a dentist new effective and convenient means for teeth occlusion study and documenting. This system is useful objective tool for medical tasks solution and further investigations are required in order to confirm effectiveness in orthodontic patients care. Ill. 5, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1658